Tuber Minerals and Phenolic Compounds in Calcium Nitrate foliar-sprayed Dioscorea alata var. Agbodo and D. rotundata var. Amula. - Otusanya, M. O. (European Journal of Applied Sciences, 2022)
Calcium Nitrate foliar spray for the management of anthracnose disease was assessed in Dioscorea alata variety Agbodo and D. rotundata var. Amula in two experiemental plots in COLPANT Farms, College of Plant Science and Crop Production, Federal University of Agriculture, Abeokuta, Ogun State in Nigeria. The design in each plot was randomized complete block (RCBD) with three replications. Mounds were 1 metre (m) by 1m and about 80cm high, with inter-replicate inter-row and intra-row spacing of 1m, 1m and 0.5m respectively. One metre (1m) clear border was maintained on each of the four sides of each plot. Each replicate had 18 plants. Calcium Nitrate foliar spray at the rates 0mgl-1, 5mgl-1 and 10mgl-1 was applied without surfactant at twelve weeks after planting (12 WAP). Anthracnose incidence and severity results are presented in another paper. But tubers in the plots were sampled at 24 WAP in order to determine, Calcium nitrate foliar spray of 5mgl-1 and 10mgl-1 without surfactant, effect on tuber minerals, namely Calcium (Ca), Magnesium (Mg), Nitrogen (N), Phosphorus (P), Potassium (K) and Sulphur (S), as well as Tuber Total Phenolic Compounds (TPC) and yield. The results of yield, TPC and the tuber minerals are presented in this paper. Statistical analysis was carried out separately for each plot. Tuber Number Per Plant (TNPP) and Tuber Weight Per Plant (TWPP) were similar across treatments for water Yam Agbodo and white guinea yam Amula. TNPP overall means are 4.43 and 3.16 for Agbodo and Amula respectively. TWPP overall means are 2.00kg (or 20.00 tonsha-1) and 1.91kg (or 19.10 tonsha-1) for Agobdo and Amula respectively. Yield (tuber fresh weight) is similar to that obtained in a report of Calcium nitrate foliar spray for anthracnose control in Dioscorea species (two improved and one local variety), but which had relatively higher spray concentrations of 0 to 12000 milligram per litre and with surfactant in the spray liquid. Tuber Ca, Mg, N and P were significantly higher in the treatments than the control in water yam Agbodo as follows: Ca in mg/100g dm is 21.48 (10mgl-1) > 19.16 (5mgl-1) > 16.31 (Control); Mg in mg/100gdm is 24.53 (10mgl-1) > 21.22 (5mgl-1) > 19.02 (control); N in percent (%) is 1.86 (10mgl-1) > 1.37 (5mgl-1) > 0.95 (control); P in mg/100g dm is 56.27 (10mgl-1) > 53.14 (5mgl-1) > 49.76 (control). K in mg/100g dm in Agbodo is 807.70 (10mgl-1) higher than 770.60 (control). S and Total Phenolic Compounds (TPC) of Agbodo were overall means 4.68% and 5.58mg Gallic Acid Equivalent per gram dry matter (5.58mgGAE/gdm) respectively. In white guinea Yam Amula, TPC and five of the minerals were higher significantly in the treatments than the control as follows: TPC in mgGAE/gdm is 5.92 (10mgl-1) > 5.39 (5mgl-1) > 4.82 (control); Ca in mg/100gdm is 18.22 (10mgl-1) > 16.45 (5mgl-1) > 14.49 (Control); N in % is 1.80 (10mgl-1) > 1.11 (5mgl-1) > 0.91 (control); P in mg/100gdm is 54.82 (10mgl-1) > 50.84 (5mgl-1) > 48.59 (control); K in mg/100gdm is 812.44 (10mgl-1) > 793.29 (5mgl-1) > 759.22 (control); S in % is 6.42 (10mgl-1) > 5.23 (5mgl-1) > 4.48 (control). Mg in white Yam Amula was overall mean of 20.19mg/100gdm, similar across treatments. A numerical comparison may be made of the two species (two varieties) because statistical analysis was carried out separately in the two experimental plots. Thus numerically (not statistically) overall means were higher in Agbodo in yield (TNPP and TWPP), TPC, Ca, Mg, N, P and K, than Amula. Amula was numerically higher in Sulphur only than Agbodo. Phenolic compounds reports of association with defence mechanisms in crop plants because they exhibit anti-fungal, anti-bacterial and anti-viral properties is discussed. Phenolic compounds reports of exhibition of antioxidant or free radical scavenging properties that boost immunity against diseases caused by free radical reactions such as cancer, diabetes, aging and cardio vascular diseases, as well as analgesic and anti-inflammatory properties is also discussed. This is to draw attention to inputs during Crop Protection Research such as this study which will effect synthesis of, or increase phenolic compounds in the edible food yams for disease resistance as well as for health benefits. Increase in calcium in this study would enhance disease resistance due to calcium role in the enhancement of the integrity of intracellular cementing materials. Magnesium and phosphorus requirement in yams is reported to be low, thus the increase in this study will ensure yams receive the optimum of the two elements. Lastly, Nitrogen and Potassium increase is to be emphasized for recommendation of 5mgl-1 and 10mgl-1 calcium nitrate foliar spray in Dioscorea species as the two are the most important for optimum yield in yams.